Effects of Gravitational Correction on Neutrino Emission from Neutron Stars - 丁文波 鄂姗姗 喻孜 张齐 戚湛强 (Chinese physics letters, 2015)
Considering the gravitational correction through introduction of weakly interacting light vector U bosons, not only the equation of state （EoS） of the neutron star matter, but also the cooling properties of neutron stars may be changed. In this work, effects of gravitational correction on neutrino emission and cooling of neutron stars in the matter with neutrons, protons, electrons, muons, △- and △0 are studied by the relativistic mean field theory and the related cooling theory. The results show that the effects are sensitive to the ratio of coupling strength to mass squared of U bosons, defined as gu. With increasing gu, the radial region where direct Urca process of nucleons can be allowed in a neutron star with the fixed mass becomes narrower, while the neutrino emissivity is somewhat higher. Moreover, the gravitational correction suppresses the effects of △- on neutrino emission. The gravitational correction leads the star to cool faster, and the higher the gu is, the faster the star cools.